2019
DOI: 10.1136/bmjopen-2018-027555
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to accessing cancer services for adults with physical disabilities in England and Wales: an interview-based study

Abstract: ObjectivesThe aim of this study was to explore the barriers to accessing cancer services faced by adults with pre-existing physical disabilities.DesignCross-sectional, exploratory qualitative study. Data were collected by semistructured interviews and analysed thematically.SettingParticipants were recruited through statutory and third sector organisations in England and Wales between October 2017 and October 2018.Participants18 people with a diagnosis of cancer and a pre-existing physical disability.ResultsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
2
12
0
2
Order By: Relevance
“…Informational support from other people with disability can help patients identify accessible medical facilities for both preventive screening and treatment, as well as identify healthcare providers equipped to manage cancer care in the context of underlying disability. Previous studies highlighted physical access barriers to cancer treatment for people with disability, notably inaccessible medical equipment, 10–13 requiring that people with disability plan ahead in anticipation of such challenges to avoid delays in care. Arranging other forms of support (i.e., identifying caregivers who could provide physical assistance with ADLs over the course of treatment) is also critical, as cancer can exacerbate mobility impairments and reduce independence with ADLs 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informational support from other people with disability can help patients identify accessible medical facilities for both preventive screening and treatment, as well as identify healthcare providers equipped to manage cancer care in the context of underlying disability. Previous studies highlighted physical access barriers to cancer treatment for people with disability, notably inaccessible medical equipment, 10–13 requiring that people with disability plan ahead in anticipation of such challenges to avoid delays in care. Arranging other forms of support (i.e., identifying caregivers who could provide physical assistance with ADLs over the course of treatment) is also critical, as cancer can exacerbate mobility impairments and reduce independence with ADLs 11 …”
Section: Discussionmentioning
confidence: 99%
“…They also experience cancer care disparities, notably lower likelihoods of receiving potentially life‐saving surgery 7 , 8 or other standard treatments 9 . Research interviews with people with disability have identified barriers to screening services and cancer care, including physical access barriers, 10‐13 inadequate preparedness among clinicians and facilities for accommodating disability, 12 , 13 and challenges navigating health promotion services for cancer survivors 14 …”
Section: Introductionmentioning
confidence: 99%
“…The availability of cancer-related counseling for patients may be limited ( Haun et al, 2018 ), e.g. by lack of transportation, living in a rural area, suffering from physical disabilities, or information deficits, which prevent cancer patients from taking advantage of face-to-face support ( Zimmermann-Schlegel et al, 2017 ; Sakellariou et al, 2019 ; Neumann et al, 2010 ). In addition, barriers on the side of psychotherapists refer to uncertainties in the treatment of somatically ill patients, organizational problems, or lack of expertise, which are reflected in low proportions of patients in psychotherapeutic practices ( Schwarz et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, few studies have explored in-depth the experiences of patients with mobility disability with the process of cancer diagnosis. [7][8][9][10][11] One such study from the United Kingdom identified broad factors within their healthcare delivery system that might affect the process of diagnosing cancer among people with mobility disability, including physical access barriers, lack of recognition of disability-related needs, and lack of consideration of aspects of living with disability that may affect cancer care (e.g., various required accommodations). 9 Thus, little information is available about important aspects of cancer care for a population that, despite relatively high rates of cancer, 3 nonetheless experiences disparities in screening and barriers to accessing care.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] One such study from the United Kingdom identified broad factors within their healthcare delivery system that might affect the process of diagnosing cancer among people with mobility disability, including physical access barriers, lack of recognition of disability-related needs, and lack of consideration of aspects of living with disability that may affect cancer care (e.g., various required accommodations). 9 Thus, little information is available about important aspects of cancer care for a population that, despite relatively high rates of cancer, 3 nonetheless experiences disparities in screening and barriers to accessing care. 4,12 To explore aspects of cancer care contributing to disability disparities, we framed our study around the model of disability adopted by the World Health Organization (WHO) in 2001.…”
Section: Introductionmentioning
confidence: 99%